Sharia’s Accounting Information Disclosure, Accountability, and Auditor Independence Effects on Stakeholder Trust: Analysis on Sharia Companies in Capital Market - Nawawi, Mohamad; Purnamasari, Pupung (Devotion : Journal of Research and Community Service, 2023)
Businesses in the food and beverage sector have strong opportunities to grow in their operations because people consume more food and beverages. In order to calculate the level of future risk, data relating to financial proportions must be worked out in other financial investigation structures. Investigating the financial challenges faced by companies in the food and beverage sector that trade conventional and Islamic stocks on the Indonesia Stock Exchange is the aim of this study. The research examines the relationship between these factors and stakeholder trust in order to understand the impact of accounting practices and auditor independence on the trustworthiness of Sharia companies. The study utilizes quantitative and associative approach. By measuring linearly and clauses to describe the relationship between two or more variables, associative research techniques are a type of research that uses statistical calculations to test hypotheses. Audit delay is one of the things that tempts businesses to change auditors. This study supports the hypothesis that organizations that experience audit delays are more likely to change auditors in the next period in an effort to win back investor confidence. The test findings show that audit opinion, audit delay, and financial strain all impact auditor turnover at the same time. The research findings show that organizations that experience accounting losses do not experience financial difficulties directly. Usually, businesses whose shares are listed on the Islamic stock index have stronger financial strength.